Effect Of Dehydration On Golf Related Performance - Hillyer, Matthew Alan (2014)
Dehydration has previously been reported to impair both cognition and sports related performance, with most studies conducted in temperate conditions. To our knowledge there have been no studies focusing on the effect of dehydration on golf related performance in warm and humid conditions. The objective of the present study was to investigate the effects of dehydration on golf related performance including hydration status, motor skill, psychomotor and cognitive performance of golfers in a warm and humid environment (29.42 ± 1.59°C, 80.5 ± 5.9% RH).